Doctor Who. [Story no. 30], The power of the Daleks [videorecording (DVD)] - Norton, Charles, 1988-; Bathurst, Peter, 1912-1989; Troughton, Patrick; Wills, Anneke, 1941- (BBC Worldwide Americas, Inc., 2017)
Lost since its premiere on the BBC 50 years ago, this six-part Classic Doctor Who story has been meticulously animated based on the original audio recordings! One of the most celebrated Classic adventures, features the regeneration (or as it was called at the time "renewal") of First Doctor William Hartnell into Second Doctor Patrick Troughton. The Doctor and his companions Polly and Ben battle the Daleks, his oldest and most dreaded foe, on the planet Vulcan.